PRM index: a customer satisfaction enhancement tool for Indian automobile sector. (2017) - Agarwal, Anuja; Singh, Deepali; Agrawal, Gaurav
This study has proposed a Partner Relationship Management (PRM) index including the impact of relationship between manufacturers and channel partners on customers in Indian automobile sector. In-depth interviews and a standard methodology for scale development were followed by extensive literature review. Questionnaire survey of automobile customers, manufacturers and channel partners belonging to NCR and southern region of India was carried out. Initially for proposing PRM framework, a total of 330 responses were collected and analysed by carrying out factor analysis. Then for proposing PRM index, a case-based methodology was used, with a total of 91 (customers) and 53 (employees of automobile organisations) responses. The major factors identified include trust, commitment enhancement, customer intimacy, relationship enhancement and customer orientation. The proposed index will help in judging the impact of services on customers and possible areas for improvement with prime motive of enhancing the customer satisfaction scores on a continual basis.